2010
DOI: 10.1021/cg900920q
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Synthesis and Magnetic Properties of Monodisperse Fe3O4 Nanocubes

Abstract: Monodisperse Fe3O4 nanocubes have been successfully synthesized by a facile solvothermal method at 260 °C in the presence of oleic acid and oleylamine. Well-defined assembly of uniform Fe3O4 nanocubes with an average size of 12 nm could be obtained without a size-selection process. The shape of as-prepared Fe3O4 nanoparticles could be reversibly interchanged between spheres and cubes by adjusting the reaction parameters. The phase structures, morphologies, and sizes of as-prepared products were investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 36 publications
0
75
0
1
Order By: Relevance
“…6 Control of the size and different morphologies (spherical, octahedral and cubic) of monodisperse Fe 3 O 4 NPs is very important because these various structures generate distinct properties. 7 To understand magnetic behavior and to improve applications, careful research related to synthetic strategies and growth mechanisms of Fe 3 O 4 NPs are essential.…”
Section: Introductionmentioning
confidence: 99%
“…6 Control of the size and different morphologies (spherical, octahedral and cubic) of monodisperse Fe 3 O 4 NPs is very important because these various structures generate distinct properties. 7 To understand magnetic behavior and to improve applications, careful research related to synthetic strategies and growth mechanisms of Fe 3 O 4 NPs are essential.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement in the magnetic properties of MFO-1 nanoparticles can be attributed to their high crystallinity and magnetite structure, as demonstrated above, where the reductive environment provided by benzyl ether is a dominant contribution factor. Gao et al had reported that Fe 3 O 4 nanoparticles with high values were obtained in octadecene when excess amount of OAm was used (10 mL of OAm was used, while the amount of Fe(acac) 3 was 1 mmol) [20]. In contrast, only 1.5 mmol of OAm was used for synthesis of MFO-3.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effect of shape of MNP on their magnetic properties is not extensively studied, a few investigations have been reported in the literature on ferrite nanocubes, maghemite nanorods, NiFe wires, cobalt nanodiscs, tetrapods, and Au-MnO nanoflowers showing a strong dependence of M s on the shapes of the nanoparticles [27][28][29][30][31][32][33][34][35][36]. Higher M s values have been observed for the cubic MNP compared to the spherical MNP of the same size [37].…”
Section: Effect Of Size Shape and Compositionmentioning
confidence: 99%